Method for converting waste carbon black into regenerated conductive carbon black

By combining calcination and acid treatment, waste carbon black is converted into regenerated conductive carbon black, which solves the problem of irrecoverability of waste carbon black, achieves efficient and environmentally friendly carbon black recovery, and produces superconducting materials with high liquid absorption values. Carbon black.

CN119331437APending Publication Date: 2025-01-21SHIMING CHEM CO LTD OF HUINONG DISTRICT SHIZUISHAN CITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411447762.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The inability to recover from waste carbon black leads to potential pollution to the environment and health, and existing treatment methods such as landfill and incineration have problems such as environmental protection and resource waste.

Method used

Waste carbon black is converted into regenerated conductive carbon black through a combination of calcination and acid treatment. The specific steps include multiple calcinations and soaking in acetic acid aqueous solution, followed by suction filtration and standing precipitation, and finally high-temperature calcination to obtain restored carbon black.

Benefits of technology

It realizes the recovery of waste carbon black, removes ash, increases surface functional groups, achieves the purpose of high dispersion, and produces room temperature superconducting carbon black with high liquid absorption value, which solves the problems of environmental pollution and resource waste.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119331437A_ABST
    Figure CN119331437A_ABST
Patent Text Reader

Abstract

The invention discloses a method for converting waste carbon black into regenerated conductive carbon black, which comprises the following steps: calcining waste carbon black at 700-1000 DEG C for the first time, standing and cooling the material calcined for the first time, grinding into a powdery substance, adding the powdery substance into deionized water, uniformly stirring, standing and precipitating, skimming ash and impurities on the upper layer, and drying to obtain the regenerated conductive carbon black. Carrying out suction filtration to separate solid from liquid, and recording the obtained solid as A1; calcining the solid A1 separated by suction filtration for the second time at 700-1000 DEG C, standing and cooling the material calcined for the second time, putting the material calcined for the second time into an acetic acid aqueous solution, stirring and soaking, and performing suction filtration for solid-liquid separation to obtain a solid A2; and calcining the solid A2 separated by suction filtration at 700-1000 DEG C for the third time, and standing and cooling the material calcined for the third time to obtain the recovered carbon black. According to the method, the waste carbon black is used as a raw material, the purposes of ash removal, surface functionalization and high dispersion are gradually achieved in a mode of combining calcination and acid treatment, a brand-new waste carbon black recovery method is established, and finally the high-liquid-absorption-value room-temperature superconducting carbon black is prepared.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of conductive carbon black preparation, and specifically, relates to a method for converting waste carbon black into regenerated conductive carbon black. Background Art

[0002] Carbon black is a product of incomplete combustion or cracking of hydrocarbons. It generally refers to an aggregate of tiny carbon particles with a diameter of 10-400nm, usually containing 90%-99% carbon, and also contains a small amount of oxygen, hydrogen, nitrogen and sulfur. Carbon black has been widely used as a reinforcing agent for rubber, electromagnetic wave shielding material, antistatic material, ink pigment, battery conductive material, etc. It is an extremely important raw material in modern industrial production.

[0003] The production methods of carbon black can be divided into two categories, one is the incomplete combustion of hydrocarbons, and the other is the thermal cracking of hydrocarbons. The structural properties of freshly produced carbon black generally conform to the hexagonal crystal system, contain a two-dimensional ordered quasi-graphite structure, have a large specific surface area, high porosity, and low particle aggregation. It can be widely used in rubber reinforcement, electromagnetic wave shielding, antistatic, ink pigment, battery conductivity and other fields. However, during use, due to the continuous external pressure, friction, heat transfer, and conductivity of carbon black, its original hexagonal crystal system, two-dimensional ordered quasi-graphite structure, pores, and aggregation state undergo significant changes. After the service life of the carbon black material expires, it cannot be reused, is difficult to restore, and eventually becomes solid waste. The chemical structure of waste carbon black is significantly different from that of newly made carbon black (aromatization of condensed aliphatic cyclic hydrocarbons), that is, it contains a large amount of harmful substances such as condensed aromatic hydrocarbons, which pollutes the surrounding water sources, soil, air and other natural environments, and endangers human health and the ecological environment.

[0004] At present, the methods for treating waste carbon black are landfill, incineration, or dumping into the sea. Faced with the large amount of waste carbon black produced at home and abroad each year and its potential pollution to water, soil, and air, as well as the major theoretical problem that waste carbon black cannot be restored. Summary of the invention

[0005] The technical problem to be solved by the present application is to provide a method for converting waste carbon black into regenerated conductive carbon black, thereby realizing the recovery of waste carbon black.

[0006] In order to solve the above problems of the present application, the present application provides a method for converting waste carbon black into regenerated conductive carbon black, comprising:

[0007] Step 1, calcining the waste carbon black at 700-1000° C. for the first time, cooling the calcined material after calcination, and grinding it into a powdery substance, adding the powdery substance into deionized water, stirring it evenly, and then precipitating it, skimming off the upper ash and impurities, and then filtering it to separate the solid and liquid, and the obtained solid is recorded as A1;

[0008] Step 2, calcining the solid A1 separated by suction filtration in step 1 for the second time at 700-1000° C., placing the second calcined material for cooling and then putting it into an acetic acid aqueous solution for stirring and soaking, then filtering to separate the solid and the liquid, and the obtained solid is recorded as A2;

[0009] Step 3: calcining the solid A2 separated by suction filtration in step 2 at 700-1000° C. for the third time, and cooling the calcined material for the third time to obtain the recovered carbon black.

[0010] The concentration of the acetic acid aqueous solution is 1.5 mol / L.

[0011] The first calcination time, the second calcination time and the third calcination time are all 3 to 6 hours.

[0012] In step 2, the stirring and soaking time of the acetic acid aqueous solution is 0.5 to 2 hours.

[0013] In the step 1, the mixture is stirred evenly in deionized water and then allowed to settle for 1 to 2 hours.

[0014] Preferably, the first calcination time, the second calcination time, and the third calcination time are all 6 hours.

[0015] Preferably, the first calcination temperature, the second calcination temperature, and the third calcination temperature are all 900°C.

[0016] Preferably, the stirring and soaking time of the acetic acid aqueous solution in step 2 is 1 hour.

[0017] The beneficial effects of this application are:

[0018] This application uses waste carbon black as raw material and proposes a carbon black recovery method that combines calcination and acid treatment. Under the premise of high efficiency, environmental protection, safety and energy saving, it gradually achieves the goals of ash removal, surface functionalization, and high dispersion, establishes a new waste carbon black recovery method, and finally produces room temperature superconductive carbon black with high liquid absorption value. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 These are the SEM images of carbon black before and after restoration in Example 3: a is waste carbon black, and b is restored carbon black;

[0020] Figure 2 This is the infrared spectrum of carbon black before and after restoration in Example 3. DETAILED DESCRIPTION

[0021] The embodiments of the technical solution of the present application will be described in detail below. The following embodiments are only used to more clearly illustrate the technical solution of the present application, and are therefore only used as examples, and cannot be used to limit the protection scope of the present application. In addition, the technical features involved in each embodiment of the present application described below can be combined with each other as long as they do not conflict with each other.

[0022] Example 1

[0023] Step 1: 20 g of waste carbon black is placed in a crucible and calcined for the first time at 700° C. for 6 h. After cooling, it is ground into a powder and then put into deionized water. After stirring evenly, it is allowed to settle and the upper ash and impurities are skimmed off. Then, the solid and liquid are separated by suction filtering. The solid is recorded as A1.

[0024] Step 2: The solid A1 separated by suction filtration in step 1 is calcined a second time at 900°C for 6h, allowed to stand and cool, and then placed in a 1.5mol / L aqueous acetic acid solution with stirring and soaking for 1h, and suction filtered. The solid is recorded as A2.

[0025] Step 3: The solid A2 separated by suction filtration in step 2 is calcined for the third time at 900°C for 6h, and then allowed to cool to obtain the recovered carbon black.

[0026] Embodiments 2 to 12

[0027] The difference between Examples 2 to 12 and Example 1 is that the first calcination temperature is different, the calcination time is different, the water washing standing time is different, and the acid washing standing time is different. Other control conditions are the same as Example 1, see Table 1 for details.

[0028] Table 1 Control conditions of each step of Examples 1 to 12

[0029]

[0030] In the above examples 1 to 4, 20g of waste carbon black was placed in four crucibles, and the first calcination was performed at 700, 800, 900, and 1000°C for 6h, respectively. After standing and cooling, it was ground into a powdery substance and then put into deionized water, stirred evenly, allowed to stand and precipitate, and the upper ash and impurities were skimmed off. After suction filtration, the solid-liquid separation was performed, and then calcined at 900°C for the second time, allowed to stand and cool, and then put into 1.5mol / L acetic acid aqueous solution, stirred and soaked, suction filtered, calcined at 900°C for the third time, and allowed to stand and cool to obtain the recovered carbon black, and the indicators such as the liquid absorption value were weighed and tested. The influence of calcination temperature on the recovered carbon black in the superconducting carbon black converted from waste carbon black in the above examples 1 to 4 is shown in Table 2.

[0031] Table 2 Effect of calcination temperature on recovered carbon black

[0032]

[0033] It can be seen from Examples 1 to 4 and Table 2 that as the calcination temperature continues to increase, the hydrochloric acid absorption value continues to increase, but the yield continues to decrease. This may be because as the calcination temperature increases, the carbon powder is burned to a greater extent and a portion is lost in the reaction. Considering the influence of economic and time factors, 900°C is selected as the optimal calcination temperature.

[0034] In the above Examples 3, 5 to 7, 20 g of waste carbon black was placed in four crucibles and calcined for 3 h, 4 h, 5 h, and 6 h, respectively, at 900 ° C. as the optimal calcination temperature. After the first calcination, deionized water was added for sufficient reaction, impurities were skimmed off, and the mixture was filtered. After the second calcination and cooling, the mixture was added to the prepared acetic acid solution for sufficient reaction, and some of the oily substances from the last time were skimmed off and filtered. After the third calcination and cooling, the recovered carbon black was obtained. The weight, liquid absorption value, and the influence of calcination time on the recovered carbon black are shown in Table 3.

[0035] Table 3 Effect of calcination time on recovered carbon black

[0036]

[0037] It can be seen from Examples 3, 5 to 7 and Table 3 that by calcining the carbon black for a period of time varying from 3 to 6 hours, the data show that the liquid absorption value increases continuously with the increase of calcination time, whereas the yield decreases. The increase in time allows the carbon black to react more fully, while the loss of carbon black also increases. A higher liquid absorption value is required for research. Considering economic reasons, a longer calcination time will also increase the demand for electrical energy. Taking into account practical reasons and experimental requirements, calcination for 6 hours was selected as the optimal reaction condition.

[0038] In the above Examples 3, 8 to 9, 20 g of waste carbon black was placed in three crucibles, calcined at 900°C for 6 h, left to cool, and operated separately (filtered without water washing, washed and left to stand for 1 or 2 h). The unwashed carbon black directly entered the acid leaching step, filtered and calcined again to obtain the product, and the carbon black in the water-washed and left to stand for 1 h treatment step was filtered and calcined, cooled and acid-leached, filtered and calcined, and cooled to obtain the desired product. The yield was monitored, the liquid absorption value was tested, and the effect of water washing on the recovered carbon black was shown in Table 4.

[0039] Table 4 Effect of water washing on recovered carbon black

[0040]

[0041] From Examples 3, 8 to 9 and Table 4, it can be seen that water washing is an indispensable part of this process, and the soaking time has little effect on the process. This may be because the suspended matter is skimmed off after water washing to reduce its influence on the monitoring of hydrochloric acid absorption value. The carbon black after high-temperature calcination has ash and other impurities. Water washing reduces the influence of impurities on the experimental results. The soaking time has little effect on the yield. Considering the time cost, the water washing soaking time of 1h is better.

[0042] In the above Examples 3, 10 to 12, 20 g of waste carbon black was placed in four crucibles, calcined at 900°C for 6 h, cooled, washed, filtered, and calcined twice. The operations were performed separately using a 1.5 mol / L aqueous acetic acid solution (no acid leaching, acid leaching for 0.5 h, acid leaching for 1 h, and acid leaching for 2 h). The non-acid leaching experimental group did not need to be calcined again to directly obtain the product, and the experimental group that required acid leaching was acid leached, filtered, and calcined again. The recovered carbon black was obtained by cooling, and the liquid absorption value and yield were tested. The effect of acid leaching time on the recovered carbon black is detailed in Table 5.

[0043] Table 5 Effect of acid leaching time on recovered carbon black

[0044]

[0045] It can be seen from Examples 3, 10 to 12 and Table 5 that acid leaching has a good effect on the experimental process. Acid leaching can wash away oily substances contained in carbon black. The use of acetic acid aqueous solution for a short period of immersion fails to fully react, leaving some impurities residual, thus affecting the hydrochloric acid absorption value. The data show that acid leaching for 1 hour is more suitable for the process of recovering carbon black.

[0046] The test data of the waste carbon black used in the above Example 3 and the recovered carbon black obtained are detailed in Table 6.

[0047] Table 6 Carbon black test data

[0048]

[0049] As shown in Table 6, the data of carbon black before and after restoration have changed to a large extent, among which the liquid absorption value required by the process has also changed greatly. After the improvement of this process, the value of waste carbon black has been improved to 4.0, reaching the national standard, and has not been changed by experimental operation. The oil absorption value reflects the degree of aggregation of carbon black particles. This indicator plays an important role in affecting the process and performance of carbon black compound rubber. Ash content is an important indicator for judging the quality of carbon black by burning organic impurities at high temperature. Heating loss is an indicator for determining the moisture content of carbon black. Many standard tests can more intuitively determine whether the carbon black after process improvement is suitable for different industries.

[0050] like Figure 1Schematic diagram a is the SEM image of carbon black before restoration, and b is the SEM image of carbon black after modification by Example 3. Characterization phenomenon It can be observed that the particle size has changed, which may be partially affected and changed by the grinding process in the processing step.

[0051] like Figure 2 As shown, a and b are the infrared detection results, where a is the waste carbon black before restoration, and b is the carbon black restored according to the process of Example 3. It can be observed that the functional groups before and after restoration have not undergone significant changes. It can be seen that in terms of chemical structure, the process used in the experiment has not caused a significant impact on the carbon black.

[0052] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.

Claims

1. A method for converting waste carbon black into regenerated conductive carbon black, characterized in that: include: Step 1, calcining the waste carbon black at 700-1000° C. for the first time, cooling the calcined material after calcination, and grinding it into a powdery substance, adding the powdery substance into deionized water, stirring it evenly, and then precipitating it, skimming off the upper ash and impurities, and then filtering it to separate the solid and liquid, and the obtained solid is recorded as A1; Step 2, calcining the solid A1 separated by suction filtration in step 1 for the second time at 700-1000° C., placing the second calcined material for cooling and then putting it into an acetic acid aqueous solution for stirring and soaking, then filtering to separate the solid and the liquid, and the obtained solid is recorded as A2; Step 3: calcining the solid A2 separated by suction filtration in step 2 at 700-1000° C. for the third time, and cooling the calcined material for the third time to obtain the recovered carbon black.

2. The method according to claim 1, characterized in that The concentration of the acetic acid aqueous solution is 1.5 mol / L.

3. The method according to claim 1, characterized in that The first calcination time, the second calcination time and the third calcination time are all 3 to 6 hours.

4. The method according to claim 1, characterized in that: In step 2, the stirring and soaking time of the acetic acid aqueous solution is 0.5 to 2 hours.

5. The method according to claim 1, characterized in that The first calcination time, the second calcination time, and the third calcination time are all 6 hours.

6. The method according to claim 1, characterized in that The first calcination temperature, the second calcination temperature and the third calcination temperature are all 900°C.

7. The method according to claim 1, characterized in that In step 2, the stirring and soaking time of the acetic acid aqueous solution is 1 hour.

8. The method according to claim 1, characterized in that In the step 1, the mixture is stirred evenly in deionized water and then allowed to settle for 1 to 2 hours.